Analisis terhadap Dua Puisi Penyair Amerika Claude McKay: Penelusuran SelukBeluk Kekuasaan Ras - Gindho Rizano (Politeknik Negeri Padang, 2014)
This article discusses two representative poems by a famous African-American writer, Claude Mckay. It seeks to interpretthe poems, “If We Must Die” and “Enslaved”, which both explore the issues racism and mental slavery, in the light of politicalapproaches such as Marxist criticism and postcolonialism. The main findings of this article are: 1) that racism and violence that itentails are rooted in class conflict and 2) that McKay’s poems can be seen as a counter-hegemony of the ethnocentricity of whiteculture. Generally, it is hoped that this writing can promote historical and political readings of minority poets like Claude McKay.